The workers' movement and the national question in Ukraine 1897-1918 - Bojcun, Marko 1951- (Leiden ; Boston Brill, 2021)
"Bojcun explores the social democratic workers' movement in the Ukrainian provinces of the Russian Empire and its impact on the course of the 1917 Revolution. The focus here is on the Ukrainian, Jewish and Russian parties, the sections of the labour movement they built, the national inequality and oppression that they confronted and the political solutions they pursued. They are examined from their inception during Russia's first drive to industrialise to the First World War, the collapse of the Russian autocracy in February 1917, the overthrow of the Provisional Government in October and establishment of the Ukrainian People's Republic in Kyiv, to the military occupation of Ukraine by Germany and Austro-Hungary in the spring of 1918."
State Power and the Development of Capitalism -- The Working Class -- Social Democracy and the National Question -- February to October 1917 -- November 1917: Attempts at Reconciliation -- December: The Failure of Reconciliation -- The First Treaty of Brest Litovsk -- Battles for Kyiv -- Kyiv under Bolshevik Rule -- The Pogroms in March and April 1918 -- Resistance to the Austro-German Occupation -- Last Days of the Rada
E-Book / Zugriff nur im DHI-Lesesaal
Keywords: Arbeiterbewegung; Sozialdemokrat; Ukraine